Pengujian Beberapa Bakteri Penghambat Pertumbuhan Xanthomonas oryzae pv. oryzae pada Tanaman Padi - Zuraidah Zuraidah (Universitas Syiah Kuala, 2013)
Bacterial leaf blight (BLB) disease caused by plant pathogenic bacteria Xanthomonas oryzae pv. oryzae (Xoo) could lead to death of rice plants. Control of plant pathogenic bacteria can be performed using biological control agents. The aim of this research was to study the inhibitory ability of eight isolates of biocontrol bacteria against Xanthomonas oryzae pv. oryzae (Xoo) under greenhouse conditions. Isolates of biological agents used in the study were obtained from IPB Culture Collection (IPBCC), Department of Biology, IPB and microbial gene bank collection of Indonesian Center for Agriculture Biotechnology and Genetic Resources (BB Biogen), consisting of Pseudomonas aeruginosa C32a and C32b, P. fluorescens ATCC 13525 Pf , Serratia marcescens E31, Bacillus sp. I.5, B. cereus I.21 and II.14, and B. firmus E65 isolates. The methods used in the research i.e. hypersensitivity test, antagonistic test of biocontrol bacteria to Xoo, and in vivo application of biological agents in the greenhouse condition. Hypersensitivity test on tobacco plants using C32a and C32b inoculums showed characteristics of slightly leaf yellowing but did not cause necrosis. Injection using Xoo inoculum showed necrosis on tobacco leaves. Antagonist isolates i.e. C32a, C32b, Pf, I.21, and I.5 showed inhibitory activity against Xoo, whereas others isolates did not show inhibitory activity. In greenhouse experiments IR 64 rice plants were sprayed with biological control agents (107cfu/ml) at 7 days, 14 days, 28 days, and 42 days after planting. The results showed that C32a isolate could suppress better the lesion length of BLB than that of chemical control (copper sulphate).